Linking individual foraging behavior and population spatial distribution in patchy environments: a field example with Mediterranean blue tits (Oecologia, 1997)
In spite of recent theoretical interest, few field studies have addressed the links between individual behavioral decisions and population distribution. This work analyzes the foraging behavior of individuals and the spatial distribution of a population of blue tits (Parus caeruleus) just before the main breeding season, when blue tit foraging was not affected by central-place or flocking behaviors. The study was carried out in open holm oak Quercus ilex woodlands (dehesas) that are patchy for canopy-foraging birds because of the scattered arrangement of trees. Residence time on each tree was not correlated either with previous flight time or with prey abundance in trees. Flight distances between trees were larger than average distances estimated in random samples of holm oaks taken close to foraging birds. Trees were not selected by birds on the basis of their expected energy costs and rewards. Bird abundance was not related to food availability in trees or to tree size across dehesas. However, bird abundance was strongly correlated with tree density and with the availability of tree holes for nesting, to the extent that the proportion of tits matched the proportions of both tree abundance and hole abundance across study plots. Overall, neither the behavior of individuals nor the distribution of the population of blue tits corresponded with food resources, which appeared superabundant; instead, tits appeared to behave and be distributed according to the distribution of structural resources such as trees and tree holes for nesting.